THE ROLE OF ENGLISH FOR HOSPITALITY WITHIN THE 'SIDE DUTIES' PROGRAM IN FOSTERING STUDENTS' CAREER READINESS: A CASE STUDY AT SMK MUTIARA TERPADU PALABUHANRATU - Widia Kustiani Waluya; Anisa Septia Megawati; Anisa Alawiyyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of English for Hospitality Purposes (EHP), integrated within the Side Duties Program (SDP), in fostering the career readiness of Grade XII Hotel Accommodation students at SMK Mutiara Terpadu Palabuhanratu. The study is motivated by the persistent gap between the General English instruction commonly delivered in vocational high schools and the specialized communicative demands of the international hospitality industry. A qualitative case study design was employed. Data were collected through in-depth, semi-structured interviews with five Grade XII students who had completed Field Work Practice (PKL) at three star-rated hotels in West Java, together with one Productive Hospitality teacher who supervises the program. Data were analyzed using the interactive model of data condensation, display, and conclusion drawing, with credibility established through source triangulation and member checking. The findings show that EHP is integrated into the Side Duties Program contextually and on a needs basis, with department-specific language content for Front Office, Food and Beverage Service, and Housekeeping. Students reported a substantial rise in English-speaking confidence, from baseline levels as low as 2 out of 10 to post-internship levels as high as 9.8 out of 10, and rated their overall career readiness between 8 and 9.8 out of 10. However, all student participants identified difficulty in comprehending diverse international accents and variable speech rates as the most significant unresolved challenge. The study concludes that the Side Duties Program is an effective work-based model for developing EHP competence and career readiness, but requires further strengthening through authentic multi-accent listening exposure, increased spontaneous speaking practice, and structured reflective learning.